Mapping Business English Researches Globally: A Bibliometric Analysis Using VOS Viewer - Niswatin Nurul Hidayati (University of Surakarta, 2023)
The specific objectives of this study are 1) to describe the global business English research overview, 2) to describe business English research and Co-Authorship in English, and 3) to indicate research gaps and provide recommendations for further research in Business English. This was literature review research. The database in this research was the Scopus database which is accessed via https://www.sciencedirect.com/ page, and the data were articles published in Scopus. The data was analysed using VOSviewer software. The results of this research indicated that this research was related to the possibility of future research related to Business English, for example in general, when talking about Business English, the research setting in Indonesia was still limited to Scopus. It could be seen that the setting was still dominated by China and Singapore. In addition, Business English was closely related to the field of professional communication both in oral and written language. Then, the context of Business English research was focused on higher education, and has not touched on vocational high schools, where graduates are prepared to enter the world of work, for example, vocational high schools in the fields of hospitality, health and so on.